2016
DOI: 10.1111/1348-0421.12373
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rates of fecal colonization with extended‐spectrum beta‐lactamase‐producing enterobacteria among patients in different wards, outpatients and medical students

Abstract: Because asymptomatic carriage of extended-spectrum beta-lactamase (ESBL) producers is a risk factor for infection, data on colonization dynamics are important when planning infection control. This study investigated fecal colonization with ESBL producers among inpatients, outpatients and medical students and compares the characteristics of ESBL producers among these groups. Carriage rates were investigated in 5581 fecal samples; 4343 from inpatients (330, 1397, 619 and 1864 from adult ICUs [intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
2
10
1
Order By: Relevance
“…Antibiotic resistant E. coli silent carriage has been described, with rates varying between 6 and 63 % in different parts of the world [8]. Particularly in university students, colonization by extended-spectrum beta lactamase (ESBL)producing bacteria have been described in Hungary (2,6 %), Sweden (7 %) and ESBL and/or AmpC in Mozambique (20 %) [6,9,10]. Previous antibiotic consumption and recent travel to countries with high antibiotic resistance rates have been associated with colonization, although the association with food, contact with animals and human patients, is not well known [2,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistant E. coli silent carriage has been described, with rates varying between 6 and 63 % in different parts of the world [8]. Particularly in university students, colonization by extended-spectrum beta lactamase (ESBL)producing bacteria have been described in Hungary (2,6 %), Sweden (7 %) and ESBL and/or AmpC in Mozambique (20 %) [6,9,10]. Previous antibiotic consumption and recent travel to countries with high antibiotic resistance rates have been associated with colonization, although the association with food, contact with animals and human patients, is not well known [2,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Extended-spectrum β-lactam (ESBL) resistant E. coli are of particular public health concern [ 19 ] as they are able to inactivate most β-lactam antimicrobials [ 20 ] used to treat associated infections. Presently, ESBL bacteria are a common source of therapeutic failure due to frequent co-resistance to multiple last resort antimicrobials [ 21 , 22 ] including colistin (i.e., polymyxin E), aminoglycoside, and 3rd and 4th generation cephalosporins that are used to treat a significant proportion of nosocomial infections [ 23 , 24 , 25 ]. In veterinary and human medicine, the extended-spectrum cephalosporins which are a sub-class of ESBL are regarded as critically important [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Colonization with ESBL-PE has been identified as an important risk factor for invasive infections with ESBL-PE, [10][11][12] and different studies have shown that ICU patients have a particularly high risk of ESBL-PE colonization. 13,14 To inform recommendations on empirical use of carbapenems in the ICU setting, strategies for identifying patients at risk for ESBL-PE are needed. Thus, screening ICU Patients for ESBL-PE carriage on admission is a logical strategy.…”
mentioning
confidence: 99%